Research methods a tool for life - Beins, Bernard (Pearson, 2013)
Research Methods: A Tool for Life introduces readers to the importance of scientific research in every day life. Updated in the third edition, this text presents current research that engages students with familiar issues. Discussions of controversies in psychology stimulate student interest while explaining important methodological concepts, which helps students understand how new research emerges.